2014
DOI: 10.1037/cfp0000016
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from infidelity: Differentiation of self, trauma, forgiveness, and posttraumatic growth among couples in continuing relationships.

Abstract: Clinicians and researchers report that individuals can heal from the trauma of infidelity and that forgiveness and even personal growth are possible after infidelity takes place. However, research has not explored specific variables that should relate to these outcomes. We defined personal growth as posttraumatic growth (PTG) and examined the relationships of differentiation of self from family of origin, trauma, forgiveness, and PTG in a sample of individuals remaining in a relationship in which infidelity ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 58 publications
2
29
0
4
Order By: Relevance
“…However, noting that participants in forgiveness interventions showed no improvement in their relationship with the perpetrator of the transgression, Lundhal et al () suggested that forgiveness interventions may “not be consistently better than no treatment in improving relationships” (p. 474). Besides confusing forgiveness with reconciliation, this conclusion counters clinical observations in which forgiveness emerges as critical for reconciliation after major relationship transgressions such as infidelity (see Baucom, Snyder, & Gordon, ), a viewpoint supported by survey data (Heintzelman, Murdock, Krycak, & Seay, ).…”
Section: Forgiveness Interventions: Efficacy (T2 Translation)supporting
confidence: 43%
“…However, noting that participants in forgiveness interventions showed no improvement in their relationship with the perpetrator of the transgression, Lundhal et al () suggested that forgiveness interventions may “not be consistently better than no treatment in improving relationships” (p. 474). Besides confusing forgiveness with reconciliation, this conclusion counters clinical observations in which forgiveness emerges as critical for reconciliation after major relationship transgressions such as infidelity (see Baucom, Snyder, & Gordon, ), a viewpoint supported by survey data (Heintzelman, Murdock, Krycak, & Seay, ).…”
Section: Forgiveness Interventions: Efficacy (T2 Translation)supporting
confidence: 43%
“…Heintzelman, Murdock, Krycak, and Seay () studied 587 people who were still in relationships with their partner in which sexual infidelity had occurred at least 6 months prior. They examined interpersonal factors that impacted healing from relational betrayal such as: differentiation of self, trauma, forgiveness, and posttraumatic growth.…”
mentioning
confidence: 99%
“…Empirical support for the relationship between forgiveness and posttraumatic growth to date is largely supportive. Research suggests that forgiveness predicts posttraumatic growth in individuals who have experienced a range of significant interpersonal offenses (Heintzelman, Murdock, Krycak, & Seay, 2014;Schultz, Tallman, & Altmaier, 2010;Wusik, Smith, Jones, & Hughes, 2015). Experimental evidence shows that writing about the benefits of an interpersonal offense or benefits of forgiveness (i.e., identifying posttraumatic growth) causes increases in forgiveness (Crowley, 2014;McCullough, Root, & Cohen, 2006).…”
Section: Forgiveness and Posttraumatic Growthmentioning
confidence: 99%